2015
DOI: 10.1097/bpo.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

Serial Derotational Casting in Congenital Scoliosis as a Time-buying Strategy

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 25 publications
2
38
0
4
Order By: Relevance
“…The mean correction rate was 20.52 ± 9.30% for CS group, which was far below than that of non-CS patients (47.53 ± 13.40%). Consistently, Demirkiran et al have reported a similar correction rate of 22% in 11 CS patients receiving casting treatment [18]. It is worth mentioning that even though the difference in precast Cobb angle between groups did not reach statistical significance, the degree of scoliosis was larger in CS group than in non-CS group by about 10° (58.54 ± 17.55 vs. 48.97 ± 13.98, P  = 0.175).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The mean correction rate was 20.52 ± 9.30% for CS group, which was far below than that of non-CS patients (47.53 ± 13.40%). Consistently, Demirkiran et al have reported a similar correction rate of 22% in 11 CS patients receiving casting treatment [18]. It is worth mentioning that even though the difference in precast Cobb angle between groups did not reach statistical significance, the degree of scoliosis was larger in CS group than in non-CS group by about 10° (58.54 ± 17.55 vs. 48.97 ± 13.98, P  = 0.175).…”
Section: Discussionsupporting
confidence: 58%
“…Serial casting has been regarded as an effective treatment to delay the need for first surgery for EOS patients [17, 18]. Fletcher et al have reported that 8 out of 29 EOS patients receiving casting correction have an average of 39 months of delayed surgery [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serial casting applied to young children with nonidiopathic EOS has been shown to be an effective way to delay surgical treatment. [26][27][28] In 1 study, curve resolution was rare with serial casting in the nonidiopathic EOS, but progression of the curve was controlled sufficiently to delay spine surgery for at least 2 years. Normal longitudinal growth of the spine was observed while the patient was in the cast.…”
Section: Current Treatment Strategies: Nonoperativementioning
confidence: 99%
“…Korsette werden die durch Fehlbildungen entwickelten Krümmungen nicht beeinflussen, sie eignen sich nicht zur Wachstumslenkung. Es finden sich wenige Literaturhinweise zur konservativen Behandlung dieses Krankheitsbildes [5,35]. Die Wirksamkeit einer Korsettbehandlung kann bei diesen Krankheitsbildern nicht die einer Operation erreichen.…”
Section: Korsetttherapieunclassified